Correlation between Fear of Missing Out and Academic Stress Medical Students Tanjungpura University - Wanda Ayuditha Noor Alifia; Sukmawati, Fitri; Hermawati, Ery (Graduate Program Magister Manajemen Pendidikan, 2025)
Students tend to be at risk of experiencing mental health disorders. One example of a mental health disorder is Fear of Missing Out. This feeling of fear of being left behind will trigger anxiety and end up disrupting a student's academic performance, including medical students. As a result of the disruption of academic performance, it will end in academic stress. This study was an observational analytical study with a cross-sectional design. The research sample consisted of 168 medical students selected using the proportionate stratified random sampling technique. Variables were measured using the Fear of Missing Out questionnaire and the Student Academic Stress Scale (SASS). The analysis was conducted using the Spearman correlation test. Most students had high levels of FOMO (81,5%) and were not academically stressed (54,2%).The results indicated a significant positive correlation with a moderate strength between FOMO and academic stress among medical students in the Medical Study Program, Faculty of Medicine, Tanjungpura (p = 0.000; r = 0.492).The novelty Examining the relationship of FoMO with academic stress in medical students in a specific university setting that has not been widely studied. Focusing on a population with high academic stress makes these findings relevant for more targeted psychological interventions.